Analisis Prinsip Upah dalam Fikih Muamalah dan Keputusan Gubernur Nomor 561.7/KEP.804-KESRA/2023 tentang Upah Minimum terhadap Sistem Upah di Home Industry GRA Brother Works Kabupaten Bandung - Azkia Qurani; Malik, Zaini Abdul; Himayasari, Neng Dewi (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. The framework of thought in the study involves the concept of wage system practices in home industry companies based on the conformity of the principles of muamalah jurisprudence and the Governor's Decree Number 561.7 / KEP.804-KESRA / 2023 concerning the Minimum Wage of Regency / City of West Java Province in 2024. This research method uses a qualitative method using a juridical - normative approach, this type of research is empirical or uses field studies. The data sources used are primary data and secondary data. Data collection techniques in this study use observation, interview, documentation, and library research methods. Then, the data obtained is analyzed using analytical descriptive methods. Based on the analysis of muamalah jurisprudence in the wage system in this home industry company, it shows a violation of the principles of wages in muamalah jurisprudence, namely justice, eligibility, and virtue. Meanwhile, based on the analysis of the Governor's Decree Number 561.7/KEP.804-KESRA/2023 concerning the Minimum Wage for Districts/Cities in the Province of West Java in 2024, the wage regulations are then explained in Law Number 13 of 2003 concerning Manpower and Perppu Number 2 of 2022 concerning Job Creation, it shows that there is a violation of the nominal wage rules for businesses and micro, namely that the nominal wage should be at least a certain percentage of the average community consumption based on data sourced from authorized institutions in the field of statistics. Abstrak. Kerangka pemikiran dalam penelitian melibatkan konsep praktik sistem upah di perusahaan home industry berdasarkan kesesuaian prinsip-prinsip fikih muamalah serta Keputusan Gubernur Nomor 561.7/KEP.804-KESRA/2023 tentang Upah Minimum Kabupaten/Kota Daerah Provinsi Jawa Barat Tahun 2024. Metode penelitian ini adalah menggunakan metode kualitatif dengan menggunakan pendekatan yuridis-normatif, jenis penelitian ini adalah empiris atau menggunakan studi lapangan. Sumber data yang digunakan adalah data primer dan data sekunder. Teknik pengumpulan data dalam penelitian ini menggunakan metode observasi, wawancara, dokumentasi, dan studi kepustakaan atau library research. Kemudian, data yang didapat di analisis menggunakan metode deskriptif analitis. Berdasarkan analisis fikih muamalah dalam sistem pengupahan di perusahaan home industry ini menunjukkan pelanggaran terhadap prinsip-prinsip upah dalam fikih muamalah yaitu keadilan, kelayakan, dan kebajikan. Sedangkan berdasarkan analisis Keputusan Gubernur Nomor 561.7/KEP.804-KESRA/2023 tentang Upah Minimum Kabupaten/Kota Daerah Provinsi Jawa Barat Tahun 2024 yang kemudian aturan upah dijelaskan dalam Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan dan Perppu Nomor 2 Tahun 2022 tentang Cipta Kerja menunjukkan adanya pelanggaran terhadap aturan nominal upah bagi usaha dan mikro yaitu nominal upah seharusnya sekurang-kurangnya sebesar presentase tertentu dari rata-rata konsumsi masyarakat berdasarkan data yang bersumber dari lembaga yang berwenang di bidang statistik.